New fluphenazine analogues as inhibitors of P-glycoprotein in human lymphocyte cultures - Jaszczyszyn, Agata; Gąsiorowski, Kazimierz; Świątek, Piotr; Malinka, Wiesław; Cieślik-Boczula, Katarzyna; Petrus, Joanna; Czarnik-Matusewicz, Bogusława (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: To evaluate the inhibitory effect of 17 new analogues of FPh on the Pgp transport function, by estimation of the rhodamine 123 (Rod-123) accumulation inside cultured lymphocytes. Material and methods: Lymphocyte were cultured in the presence of a lectin (PHA; 2%, v/v), incubated with benzo[α]pyrene (B[α]P; 7.5 μM, 48 h) to induce genotoxic damage and to increase Pgp expression in the cells. Lymphocytes cultured without the tested compounds were considered as controls. Results It was established that 10 analogues of FPh, among 17 tested, significantly increased Rod-123 accumulation in lymphocytes at the concentration of 10 M. As compared to the control cultures the Pgp transport function was the most strongly inhibited by 1a, 1b, 1d, 3f, 3h and 3i analogues (approximately by 25%). Conclusions : FPh analogues 1a, 1b, 1d, 3f, 3h and 3i should be further studied as promising candidates for adjuvant cancer chemotherapeutics.